If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -4b = -18 Solving 6 + -4b = -18 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -4b = -18 + -6 Combine like terms: 6 + -6 = 0 0 + -4b = -18 + -6 -4b = -18 + -6 Combine like terms: -18 + -6 = -24 -4b = -24 Divide each side by '-4'. b = 6 Simplifying b = 6
| y^2+5*y=2 | | R(x)=-0.5x^3+2.6x^2+3x | | -4x-83=27-9x | | 2(x+8)+2x=20 | | -3/8x=1/4 | | -5/3=1/5x-1/2 | | 24=3(9-2) | | (9x-4)(4x-9)=0 | | -369=9(5x+9) | | 0=1.8*x+32 | | y-4=1/3(x-2) | | 9m+5n-3m+9n= | | 24=3(-2-2) | | b=1/5ht | | X^2-5x+20=6x-4 | | -3x+26=-7 | | 10r+100s+50t= | | 4÷1/3 | | 1/3-9/15 | | (49w^12)^1/2 | | -2-4(2-4x)=-10-2x | | (49w12^12)^1/2 | | 24=3(10-2) | | 24=3(-1-2) | | y-65=-10x+60 | | 30=-30n^2+6 | | 7/8-1/8= | | 1/3x-8=12 | | 30=-30n+6 | | 2a+7=-(2+a) | | -1/2(t=9)=53/4t=3/8t | | -6x+6(4x+6)=-116 |